1996
DOI: 10.2190/mtg0-dcce-yr29-jlt3
|View full text |Cite
|
Sign up to set email alerts
|

College Students' Smoking Behavior, Perceived Stress, and Coping Styles

Abstract: The purpose of this study was to examine college students' smoking behavior as well as their current smoking status and its effects on perceived levels of stress and coping styles. Students from four universities completed the Perceived Stress Scale, the Coping Inventory for Stressful Situations and a smoking questionnaire. Of the 1330 students who participated in the study, 19 percent were current smokers. On the Perceived Stress Scale, current smokers' mean score was significantly higher than that of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
40
1
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 12 publications
11
40
1
6
Order By: Relevance
“…Consistent with other studies, 16% of these college students indicated that they became regular smokers after 18 years of age (DeBernardo et al, 1999;Everett et al, 1999;Wechsler et al, 1998). Their reasons for beginning smoking related to stress, image, and intrigue as reported by others (Naquin & Gilbert, 1996;Schorling et al, 1994). Consistent with other studies, smokers who did not want to quit recognized that smoking had negative effects, but did not believe that these effects would occur in the near future or that quitting would be too difficult and disenfranchise them from their smoking friends (DeBernardo et al, 1999).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with other studies, 16% of these college students indicated that they became regular smokers after 18 years of age (DeBernardo et al, 1999;Everett et al, 1999;Wechsler et al, 1998). Their reasons for beginning smoking related to stress, image, and intrigue as reported by others (Naquin & Gilbert, 1996;Schorling et al, 1994). Consistent with other studies, smokers who did not want to quit recognized that smoking had negative effects, but did not believe that these effects would occur in the near future or that quitting would be too difficult and disenfranchise them from their smoking friends (DeBernardo et al, 1999).…”
Section: Discussionsupporting
confidence: 88%
“…Studies of psychological correlates of college smokers show that they are more likely to express lower life satisfaction (Emmons et al, 1998;Schorling, Gutgesell, Klas, Smith, & Keller, 1994) and have higher levels of perceived stress than former smokers or those who never smoked (Naquin & Gilbert, 1996). High levels of alcohol use both in college (Emmons et al, 1998;Schorling et al, 1994) and high school (Emmons et al, 1998) were associated with cigarette smoking among college students.…”
Section: Introductionmentioning
confidence: 96%
“…Perceived stress has been studied in a variety of contexts, such as smoking cessation (Cohen & Lichtenstein, 1990;Hajek, Taylor, & McRobbie, 2010;Naquin & Gilbert, 1996), caregiver burden (Bedini, Gladwell, & Dudley, 2011;Chwalisz, 1992;Chwalisz & Kisler, 1995), life events (Beatty, Lee, & Wade, 2009;Cohen et al, 1993;Otto et al, 1997), and leisure (Aldana, Sutton, Jacobson, & Quirk, 1996;Bedini et al, 2011;Kleiber et al, 2002;Lutz, Lochbaum, Lanning, Stinson, & Brewer, 2007). Perceived stress has also been found to relate to an assortment of psychosocial and physiological constructs, such as personality (Besser & Shackelford, 2007;Burgess, Irvine, & Wallymahmed, 2010;Candrian et al, 2008;Ebstrup, Eplov, Pisinger, & Jørgensen, 2011), affect (Besser & Shackelford, 2007;Cohen et al, 1993;Davidsdottir, 2007), self-efficacy (Ebstrup et al, 2011;Moeini et al, 2008;Trouillet, Gana, Lourel, & Fort, 2009), attachment (Cordon, Brown, & Gibson, 2009;Koopman et al, 2000;McCarthy, Moller, & Fouladi, 2001;Reiner, Anderson, Hall, & Hall, 2010), adjustment (Baker, 2004;Curtis, Groarke, Coughlan, & Gsel, 2004;Extremera, Durán, & Rey, 2007;Kulik & Heine-Cohen, 2011), depression (Candrian et al, 2008;Ghorbani, Krauss, Watson, & LeBreton, 2008;Holt-Lunstad, Birmingham, & Light, 2011), happiness …”
Section: Correlates Of Perceived Stressmentioning
confidence: 99%
“…Perceived stress has also been found to relate to an assortment of psychosocial and physiological constructs, such as personality (Besser & Shackelford, 2007;Burgess, Irvine, & Wallymahmed, 2010;Candrian et al, 2008;Ebstrup, Eplov, Pisinger, & Jørgensen, 2011), affect (Besser & Shackelford, 2007;Cohen et al, 1993;Davidsdottir, 2007), self-efficacy (Ebstrup et al, 2011;Moeini et al, 2008;Trouillet, Gana, Lourel, & Fort, 2009), attachment (Cordon, Brown, & Gibson, 2009;Koopman et al, 2000;McCarthy, Moller, & Fouladi, 2001;Reiner, Anderson, Hall, & Hall, 2010), adjustment (Baker, 2004;Curtis, Groarke, Coughlan, & Gsel, 2004;Extremera, Durán, & Rey, 2007;Kulik & Heine-Cohen, 2011), depression (Candrian et al, 2008;Ghorbani, Krauss, Watson, & LeBreton, 2008;Holt-Lunstad, Birmingham, & Light, 2011), happiness (Brief, Burke, George, Robinson, & Webster, 1988;Chatters, 1988;Feist, Bodner, Jacobs, Miles, & Tan, 1995;Schiffrin & Nelson, 2010), health related behavior (Naquin & Gilbert, 1996;Rod, Grønbaek, Schnohr, Prescott, & Kristensen, 2009;Wichianson, Bughi, Unger, Spruijt-Metz, & Nguyen-Rodriguez, 2009), and health problems (Cohen et al, 1993;Lovell, Moss, Wetherell, 2011;Nielsen et al, 2008).…”
Section: Correlates Of Perceived Stressmentioning
confidence: 99%
“…Other negative outcomes associated with stress include increased alcohol consumption (Morgan 1997), smoking (Naquin et al 1996), reduction in immune system functioning (Sarid et al 2004) and an increased tendency to consider suicide (Hirsch et al 1996). For many students perhaps the most significant response to stress is a reduction in their academic performance.…”
Section: Students' Responses To Stressmentioning
confidence: 99%